Gene sdaB Is Involved in the Nematocidal Activity of Enterobacter ludwigii AA4 Against the Pine Wood Nematode Bursaphelenchus xylophilus - Zhao, Yu; Yuan, Zhibo; Wang, Shuang; Wang, Haoyu; Chao, Yanjie; Sederoff, Ronald R.; Sederoff, Heike; Yan, He; Pan, Jialiang; Peng, Mu; Wu, Di; Borriss, Rainer; et al. (Frontiers in Microbiology, 2022)
Bursaphelenchus xylophilus, a plant parasitic nematode, is the causal agent of pine wilt, a devastating forest tree disease. Essentially no efficient methods for controlling B. xylophilus and pine wilt disease have yet been developed. Enterobacter ludwigii AA4 isolated from the root of maize has powerful nematocidal activity against B. xylophilus in a new in vitro dye exclusion test. The corrected mortality of the B. xylophilus treated by E. ludwigii AA4 or its cell extract reached 98.3% and 98.6%, respectively. Morphological changes in B. xylophilus, treated with a cell extract from strain AA4 suggested that the death of B. xylophilus might be caused by an increased number of vacuoles in nonapoptotic cell death and the damage to tissues of the nematodes. In a greenhouse test, the disease index of the seedlings of Scots pine (Pinus sylvestris) treated with the cells of strain AA4 plus B. xylophilus or those treated by AA4 cell extract plus B. xylophilus was 38.2 and 30.3, that was significantly lower than 92.5 in the control plants treated with distilled water and B. xylophilus. We created a sdaB gene knockout in strain AA4 by deleting the gene putatively encoding the beta-subunit of L-serine dehydratase through Red homologous recombination. The nematocidal and disease-suppressing activities of the knockout strain were remarkably impaired. Finally, we revealed robust colonization of P. sylvestris seedling needles by E. ludwigii AA4, which is supposed to contribute to the disease-controlling efficacy of strain AA4. Therefore, E. ludwigii AA4 has significant potential to serve as an agent for the biological control of pine wilt disease caused by B. xylophilus.